Maternal prenatal screening programs that predict trisomy 21, trisomy 18, and neural tube defects in offspring - Yiming Chen; Wenwen Ning; Yezhen Shi; Yijie Chen; Wen Zhang; Liyao Li; Xiaoying Wang (PLoS ONE, 2023)
Objective To determine the efficacy of three different maternal screening programs (first-trimester screening [FTS], individual second-trimester screening [ISTS], and first- and second-trimester combined screening [FSTCS]) in predicting offspring with trisomy 21, trisomy 18, and neural tube defects (NTDs). Methods A retrospective cohort involving 108,118 pregnant women who received prenatal screening tests during the first (9–13+6 weeks) and second trimester (15–20+6 weeks) in Hangzhou, China from January–December 2019, as follows: FTS, 72,096; ISTS, 36,022; and FSTCS, 67,631 gravidas. Result The high and intermediate risk positivity rates for trisomy 21 screening with FSTCS (2.40% and 5.57%) were lower than ISTS (9.02% and 16.14%) and FTS (2.71% and 7.19%); there were statistically significant differences in the positivity rates among the screening programs (all P < 0.05). Detection of trisomy 21 was as follows: ISTS, 68.75%; FSTCS, 63.64%; and FTS, 48.57%. Detection of trisomy 18 was as follows; FTS and FSTCS, 66.67%; and ISTS, 60.00%. There were no statistical differences in the detection rates for trisomy 21 and 18 among the 3 screening programs (all P > 0.05). The positive predictive values (PPVs) for trisomy 21 and 18 were highest with FTS, while the false positive rate (FPR) was lowest with FSTCS. Conclusion FSTCS was superior to FTS and ISTS screening and substantially reduced the number of high risk pregnancies for trisomy 21 and 18; however, FSTCS was not significantly different in detecting fetal trisomy 21 and 18 and other confirmed cases with chromosomal abnormalities.